The effect of the guided inquiry learning model on students' mathematical representation ability - Al Amin; Caswita; Mella Triana (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2025)
Mathematical representation ability is an important skill for students to transform complex problems into simpler forms. However, field observations based on the pretest results of mathematical representation ability conducted at SMP Negeri 18 Bandarlampung show that many students have not yet mastered this skill. This is supported by the 2022 PISA results, which indicate that students' mathematical representation ability is still categorized as low. Therefore, it is necessary to apply a learning model that can help students improve their mathematical representation skills. This study aims to determine the effect of the guided inquiry learning model on students' mathematical representation ability. The population in this study consisted of all eighth-grade students at SMP Negeri 18 Bandar Lampung in the odd semester of the 2024/2025 academic year, totaling 174 students distributed across six classes. Sampling was conducted using the cluster random sampling technique, selecting class VIII B (28 students) as the experimental class and class VIII D (29 students) as the control class. The research design used was the pretest-posttest control group design. The data in this study are quantitative data obtained from the students' mathematical representation ability test. Based on data analysis using the Mann-Whitney U test, it was found that the improvement in mathematical representation ability of students who participated in guided inquiry learning was higher than that of students who followed conventional learning. Thus, the guided inquiry learning model has an effect on improving students' mathematical representation ability.